230 The Impact of a Palliative Care ECHO Programme on Symptom Severity Scores and Phases Score in a Nursing Home Population. (16th September 2019) - Murphy, Claire; Molloy, Una; McLean, Sarah; Ryan, Daniel
Abstract: Background: In Ireland most deaths occur in acute hospitals however 20% of deaths occur in residential facilities. Less than 30% receive specialist palliative care input. ECHO (extension for community healthcare outcomes) is a palliative care education programme consisting of a 10 part lecture series. Twenty nursing homes and 353 staff participated. A phases score is a 5-point rating scale classifying the status of a palliative care patient ranging from stable to bereaved. Methods: Data collected by palliative care professionals from September 2017 to December 2018 was analysed. This included demographic features, a phases score and scores for pain, carer stress, spiritual and psychological need. Nursing homes that attended ≤ 3 ECHO sessions were excluded, 15 participating nursing homes were included. Age matched control subjects were selected from non-participating nursing homes on a 2:1 basis. Data was analysed using the paired T Test and Chi squared was analyzed for frequency data. Results: There were 40 patients in the intervention group and 80 in the control group. Mean ages were 83yrs and 82yrs respectively. Palliative care referral numbers did not change significantly between the two groups (111 and 114). The Phases score was significantly reduced in the ECHO group compared to controls (P=< 0.007). There was no significant reduction in the phases score in the ECHO group pre and post intervention (P=0.29). There was no difference in Pain scores between groups (P=0.98) Conclusion: The ECHO intervention led to a reduction in the overall phases score in participating nursing homes. This was not the result of increased palliative care referrals. We would infer it is a reflection of better control of symptoms overall. We did not demonstrate a significant reduction in individual symptoms. The phases score is an overall representation of a patient's status. With the expansion of the ECHO programme on-going analysis will be performed.